Fieldwork in landscape architecture : methods, actions, tools - Oles, Thomas; Horrigan, Paula (New York, NY : Routledge, 2025)
"Fieldwork in Landscape Architecture: Methods Actions Tools addresses the initial encounter between landscape designer and landscape site, an encounter that determines the entire course of the design process. The book offers a four-part framework ('what you seek,' 'what you carry,' 'how you act,' and 'what you leave behind') for learning and practicing fieldwork as a landscape design skill, and contains over sixty first-person accounts by international practitioners and educators about the methods and tools they bring to the field, from drones to dance. The first title of its kind, Fieldwork will be an invaluable resource for students and instructors of landscape architecture, as well as for anyone interested in the practice and experience of direct encounter with real places"--
What you seek -- Landscapes of sound / Brenda Brown -- Cultural excavation / Noémie Despland-Lichtert and Brendan Shea.
Keywords: Landscape design -- Fieldwork; Landscape architecture -- Fieldwork; ARCHITECTURE / Landscape